Achieving a Safe Endotracheal Tube Cuff Pressure in the Prehospital Setting: Is It Time to Revise the Standard Cuff Inflation Practice?. (3rd March 2016) - Carhart, Elliot; Stuck, Logan H.; Salzman, Joshua G.
ABSTRACT: Numerous studies have reported unsafe endotracheal tube (ETT) cuff pressures (CP) in the prehospital environment. The purpose of this study was to identify an optimal cuff inflation volume (CIV) to achieve a safe CP (20–30 cmH2 O). This observational study utilized 30 recently harvested ovine tracheae, which were warmed from refrigeration in a water bath at 85°F prior to testing. Each trachea was intubated with five different ETT sizes (6.0–8.0 mm), and each size tube was tested with six cuff inflation volumes (5–10 cc). The order of ETT size for each trachea and CIV for each size ETT was randomly pre-assigned. Data were descriptively summarized and categorized before mixed-effects logistic regression was used to determine optimal CIV. Only 113 CP measurements (12.6%, N = 900) were within the optimal range (M = 54.75 cmH2 O, SD = 38.52), all of which resulted from a CIV 6 or 7 cc (61% and 39%, respectively). CIVs of 5 cc (n = 150) resulted in underinflation (<20 cmH2 O) in all instances, while CIVs of 8, 9, or 10 cc (n = 150 each) resulted in overinflation (>30 cmH2 O) in all instances, regardless of ETT size. The odds of achieving a safe CP were greater with CIV of 6 cc for tube sizes 6.0 (OR = 15.9, 95% CI = 3.85–65.58, p < 0.01) and 6.5 mm (OR = 3.16, 95% CI = 1.06–9.39, p = 0.039); however, there was no significant difference in the odds of achieving a safe CP between CIV of 6 and 7 cc for tube sizes 7.0, 7.5, or 8.0 mm. Neither trachea circumference (M = 7.11cm, SD = 0.40), nor tissue temperature (M = 81.32°F, SD = 0.93) were found to be significant predictors of CP (p = 0.20 and 0.81, respectively). Our study showed a high frequency of CP measurements outside of the desired norms. The CIV range of 6–7 cc resulted in the highest likelihood of achieving the desired cuff pressure range, while cuffs inflated with 8–10 cc resulted in dangerously high CPs in all instances. In the absence of a more ideal solution, the results of this study suggest that narrowing the recommended CIV from 5–10 cc to 6–7 cc might be a reasonable target for any tube size.